Interactive virtual museum for Malacca state museum corporation / Syamsulhairi Yaakop - Yaakop, Syamsulhairi (2000)
The purpose of this project is to develop a system for a user to engage in a virtual visit to the gallery of the museum. The system is part of the virtual reality and multimedia environment. A virtual model of the museum gallery will be built by using a virtual reality software together with the necessary tools like a camera and video camera. Through this virtual museum, the users are able to do walkthrough of the museum galleries and view the information of the exhibits by clicking on particular objects through hot spot. This is an off-line system. Nowadays, there are a number of virtual reality application5 been implemented and can be used to support almost any human activity. The virtual museum is a photo realistic computer generated museum incorporating a display of rooms and exhibits. The visitor to the museum and the gallery or room in the museum may use a virtual visit or tour. The visitor should be able to move forward, backward, upward or downward and still be able to view all of the objects in the gallery of the museum. The design of the museum and the gallery contains on the main lobby from which one can access the adjoining gallery. The projections of these objects would include also the various effects of lighting, distance, rotation and other movements like zooming in and out of the gallery.